Parental alienation in light of the legislation of the State of Tabasco, Mexico (Revista de Investigaciones Universidad del Quindío, 2020)
Parental Alienation (PA) is a subtle form of violence that occurs mostly within separations or divorces; it is a type of discredit and rejection, openly or covertly, when speaking or acting in a disqualifying or destructive manner of the other parent. While Parental Alienation Syndrome (PAS) has been understood as a denigration or rejection behavior on the part of the child to a parent, product of the malicious influence of one parent or even third parties. The Civil Code of the State of Tabasco mentions in three occasions the notion of "parental alienation", not as a syndrome, but in its broadest meaning, in which it places children and teenagers in a state of helplessness and vulnerability, foreseeing that parents will develop behaviors that are detrimental to the infant(s).
Keywords: Parental Alienation (PA); Parental Alienation Syndrome (PAS); Higher Interest; Child Abuse